2007
DOI: 10.1614/wt-060178.1
|View full text |Cite
|
Sign up to set email alerts
|

Sweetpotato Tolerance to Halosulfuron Applied Postemergence

Abstract: Studies were conducted in 2003 and 2004 to determine the effect of application timing and halosulfuron rate on sweetpotato yield and quality. Halosulfuron was applied 1, 2, and 4 wks after transplanting (WAP) sweetpotato in 2003, and 2, 3, and 4 WAP in 2004. Treatments within each timing included halosulfuron at 13, 26, 39, 52, and 65 g ai/ha plus a weed-free control. Combined over year, site, cultivar and rate, halosulfuron applied at 1, 2, 3, and 4 WAP stunted sweetpotato 32, 15, 11, and 14%, respectively, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
1
8
0
4
Order By: Relevance
“…& Nakai], and tomato (Lycopersicon esculentum Mill.) in the United States (Brandenberger et al 2005;Dittmar et al 2008;Felix and Newberry 2012;Mullinix 2002 2005;MacRae et al 2007MacRae et al , 2008Webster and Culpepper 2005).…”
mentioning
confidence: 99%
“…& Nakai], and tomato (Lycopersicon esculentum Mill.) in the United States (Brandenberger et al 2005;Dittmar et al 2008;Felix and Newberry 2012;Mullinix 2002 2005;MacRae et al 2007MacRae et al , 2008Webster and Culpepper 2005).…”
mentioning
confidence: 99%
“…Sweetpotato tolerance to POST applications of thifensulfuron (MacRae et al 2007a) and trifloxysulfuron (MacRae et al 2005) increased as application timing was delayed from 1 to 8 WAP. Similarly, MacRae et al (2007b) reported that halosulfuron-methyl applications at 4 WAP did not reduce no. 1 or total yields of Beauregard and ‘Hernandez’ sweetpotato.…”
Section: Resultsmentioning
confidence: 90%
“…The current rotational restriction for rimsulfuron/thifensulfuron is 1.5 and 18 mo for rates of up to 18/18 g ha -1 and between 18/18 to 32/32 g ha -1 , respectively (Anonymous 2017a). Acetolactate synthase-inhibitor herbicides have been investigated for use in sweetpotato, but the vast majority of investigations have focused on broadcast applications made over the top of the crop after transplanting (Dittmar et al 2013;MacRae et al 2007aMacRae et al , 2007bMeyers and Shankle 2016). Published research results reporting sweetpotato tolerance to rimsulfuron and thifensulfuron-methyl are limited.…”
Section: Introductionmentioning
confidence: 99%